Apparatus Competence in Increasing the Effectiveness of the Direct Cash Assistance Program - Palilati, Mega; Tahir, Arifin; Kamuli, Sukarman (Universitas Negeri Gorontalo, 2025)
This study aims to analyze the influence of the competence of the apparatus on the effectiveness of the direct cash assistance program in Talaga Jaya District, Gorontalo Regency. Through a quantitative approach and a path analysis method, the results of the study show that simultaneously the competence of the apparatus has a significant effect on the effectiveness of the BLT program. Partially, the three dimensions of competence that had a significant and positive effect were knowledge (15.60%), understanding (36.5%), and interest (28.5%). Meanwhile, the dimensions of ability (-3.62%), value (0.84%), and attitude (1.58%) did not show a significant influence. Understanding of the apparatus is the dominant factor in supporting the effectiveness of the program, indicating the importance of understanding the program's objectives, procedures, and objectives. Simultaneously, the competence of the apparatus affects the effectiveness of the direct cash assistance program by 78%. So that improvements in aspects of the competence of the apparatus can simultaneously affect the effectiveness of the program in terms of the accuracy of the targets, socialization, achievement of goals, and monitoring. This research also emphasizes the importance of capacity and competence development of the apparatus as the main key in ensuring the successful implementation of social assistance programs at the local level and indicates that there are external factors outside the competence of the apparatus that can affect the success of the program. Overall, these findings support the hypothesis that improving the competence of the apparatus can increase the effectiveness of the BLT program.